Choral-conductor training of future teachers in the Poltava institute of national education (1921–1941) - Dem’yanko, Nataliya (ScienceRise: Pedagogical Education, 2017)
In the article is considered the state of choral-conductor training of a future teacher in educational institutions of the end of ХІХ – beginning of ХХ century (teacher institutes and seminaries), especially in the Poltava institute of national education (1921–1941). Its components were determined and characterized (theoretical training, methodology of vocal-choral work, choral conducting, choral singing). There were elucidated the content (formation of conducting, vocal-choral knowledge, abilities and skills, use of diverse choral repertoire), forms (lectures and practical activities, concert performances, conducting-choral practice, discussions, debates) and methods (creation analysis, instrumental execution of score, signing of parts, conducting of creation, work with chore) of conductor-choral training by teachers of the department of art studies under the guidance of the famous Ukrainian teacher, musical expert, ethnographer, choreographer, conductor and composer V.M. Verkhovinets. There was grounded its effectiveness in the process of future teacher’s professional competences formation. There were elucidated the content and character of creative activity of the student chore of the Poltava INE (executive, theoretical, methodological and cultural-educational aspects) in the aforesaid historical period